1994
DOI: 10.1029/94jc01170
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic patterns of seasonal and interannual temperature variation off the west coast of the United States: Local and remote large‐scale atmospheric forcing

Abstract: Remote forcing from the equatorial Pacific and local forcing from the North Pacific lead to interannual ocean temperature change along the west coast of the United States. In fall‐winter seasons, coherent temperature changes extending from the surface to 300 m depth indicate remote forcing. Correlations between time series of ocean temperature change and series of equatorial sea level pressure (SLP) at 12.4°S × 130.9°E were as great below 100 m as at the surface. From 1954 to 1986, coherent warming events occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 47 publications
3
47
0
Order By: Relevance
“…Coastal upwelling continues but the waters recruited are low in nutrients, and productivity declines sharply. The coastal upwelling system of the northeast Pacific is also affected by El Niño, but the developmental sequence of events remains poorly described, and there is continued debate over the primary forcing (Norton & McLain, 1994;Simpson, 1984;Wooster & Fluharty, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Coastal upwelling continues but the waters recruited are low in nutrients, and productivity declines sharply. The coastal upwelling system of the northeast Pacific is also affected by El Niño, but the developmental sequence of events remains poorly described, and there is continued debate over the primary forcing (Norton & McLain, 1994;Simpson, 1984;Wooster & Fluharty, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…An analysis by Norton & McLain (1994;see also Norton et al 1994) provides the basis for exploring the more remote factors that affect local ocean conditions and ultimately the food web of coastal central California. Using time-series analysis, these authors found significant correlation between water temperatures in the upper 300 m of the water column off California and 2 ocean-atmosphere systems: atmospheric pressure in Darwin, Australia, as part of the Southern Oscillation (SO), and pressure at 45"N, 165"W, as part of the Aleutian low (hereafter called the Aleutian low pressure system index, or AL), 1954 to 1986.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly anomalous warming and cooling patterns in the North Pacific result from complex interactions between atmospheric and oceanic processes in the tropics and extratropics. Norton and McClain (1994) conclude that warming episodes associated with equatorial forcing events are more likely to be detected at depth (>lo0 m), because of oceanic long waves, whereas warming associated with local forcing is more likely to be detected at the surface, and the most pervasive regional ocean warming effects during the fall-winter cooling season are associated with the equatorial atmosphere. Maximum warming (in the northern coastal Cahfornia Current) occurs in the fall-winter season following the tropical El Niiio initiated in the previous December through July.…”
Section: Discussionmentioning
confidence: 87%
“…Some aspects of this association are worth investigating further, including similarities in the life histories of these species, the effect of longwave propagation up the slope during strong ENSO events, the tendency for equatorial forcing to be felt more strongly at depth (Norton and McClain 1994), and transport of abundant large oceanic copepods shoreward (McFarlane and Beamish 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation